RONC-13. Change in hippocampus volume as a function of radiation dose: Results from a prospective trial with standardized imaging and morphometric evaluation. (3rd June 2022) - Hall, Matthew; Odia, Yazmin; Von Werne, Katherine; Niazi, Toba; Maher, Ossama; Khatib, Ziad; Mohler, Alexander; Kotecha, Rupesh; Kalman, Noah; Tom, Martin; Abrams, Kevin; Naidoo, Reshma; et al.
Abstract: PURPOSE/OBJECTIVES: MRIs were prospectively collected at baseline and during follow-up in pediatric and young adult brain tumor patients (Age<35) to measure volumetric changes in multiple brain substructures with neurocognitive, laboratory, and quality-of-life assessments. In this planned interim analysis, we model early outcomes for change in hippocampal volume at 6 and 12 months following radiotherapy. MATERIALS/METHODS: As of 2/6/2021, 60 patients enrolled on this prospective study and 41 completed 6 and 12-month post-treatment assessments after fractionated intensity-modulated proton therapy. Left and right hippocampus volumes were independently measured on T1 sagittal precontrast MRI at baseline, 6-months, and 12-months after radiotherapy using automated software and physician-delineated contours. The relationship between mean hippocampus dose and change in volume was assessed by Pearson's correlation coefficient. A linear mixed-effects model was applied to evaluate other predictors associated with change in hippocampal volume, assuming random effects of subjects. RESULTS: Mean hippocampus dose was strongly correlated with change in hippocampal volume at 12 months following radiotherapy (r=−0.707, 95% CI [-0.805, -0.572], p<0.001). Changes in hippocampal volumes over time were similar between software and physician contours. In the mixed-effects model, only mean hippocampus dose was significantly associated with hippocampal volume change (p<0.001) at both 6 and 12 months. The final model predicted changes in hippocampal volume of -3.6% and -10.1% for every 10 Gy increase in mean dose at 6 and 12 months, respectively. Hippocampal volume was significantly reduced for mean doses >5 Gy (meanΔ -38.1%±20.3%, p<0.001), while no significant volume change was observed with mean doses ≤5 Gy (meanΔ -1.7%±5.0%). CONCLUSIONS: Change in hippocampal volume was correlated with hippocampus mean dose at 6 and 12 months following radiotherapy. Future analyses will assess volumetric changes in additional brain substructures as a function of radiation dose and correlate with measured neurocognitive and quality-of-life effects.